2020
DOI: 10.1029/2019gb006397
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Chromium Redox and Stable Isotope Composition in the Surface Ocean

Abstract: While chromium stable isotopes (δ 53 Cr) have received significant attention for their utility as a tracer of oxygen availability in the distant geological past, a mechanistic understanding of modern oceanic controls on Cr and δ 53 Cr is still lacking. Here we present total dissolved δ 53 Cr, concentrations of Cr (III) and total dissolved Cr, and net community productivity (NCP) from the North Pacific. Chromium concentrations show surface depletions in waters with elevated NCP, but not in lower productivity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 80 publications
4
51
0
Order By: Relevance
“…This also permitted the application of stable Cr isotopes as a proxy for past changes in oceanic and atmospheric oxygenation (e.g., Frei et al, 2009;Planavsky et al, 2014). Recent investigations revealed that biologically mediated redox reactions may play an important role in the marine Cr cycle (Huang et al, 2021;Janssen et al, 2020;Semeniuk et al, 2016), and the isotopic ratio measured in marine sediments may hence be potentially used for the reconstruction of past changes in biological productivity.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This also permitted the application of stable Cr isotopes as a proxy for past changes in oceanic and atmospheric oxygenation (e.g., Frei et al, 2009;Planavsky et al, 2014). Recent investigations revealed that biologically mediated redox reactions may play an important role in the marine Cr cycle (Huang et al, 2021;Janssen et al, 2020;Semeniuk et al, 2016), and the isotopic ratio measured in marine sediments may hence be potentially used for the reconstruction of past changes in biological productivity.…”
Section: Introductionmentioning
confidence: 99%
“…In the modern ocean, total dissolved Cr concentrations of unpolluted waters typically range between 1 and 6 nmol kg -1 (e.g., Jeandel and Minster, 1987;Nasemann et al, 2020) of which a majority (>70 %) is generally found in the soluble Cr(VI) redox state. Reduction of Cr(VI) is either induced in poorly oxygenated waters and/or catalyzed by Fe(II) and organic matter in oxic waters (Janssen et al, 2020;Kieber and Helz, 1992). As such, Cr(III) concentrations can account for the majority of total dissolved Cr in OMZs (Huang et al, 2021;Rue et al, 1997), and may also be elevated in high productivity surface waters (e.g., Janssen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations